Designing a Research Methodology to Assess Youth Readiness for AI-Driven HR Practices in Latvia - Khlud, Veranika; Reshina, Galina (Acta Universitatis Lodziensis. Folia Oeconomica, 2025)
The purpose of the presented study is to develop a comprehensive research methodology for evaluating the readiness of young professionals in Latvia to work within AI-enhanced human resource (HR) environments. As artificial intelligence is increasingly embedded in recruitment and talent management processes, understanding how prepared youth are to engage with such systems is both timely and essential. The study applies a mixed-methods design, combining quantitative surveys with qualitative semi-structured interviews and focus groups. The survey instrument is structured to assess digital skills, awareness of AI in HR, trust in algorithmic systems, and adaptability. The qualitative component provides contextual insight into perceptions and personal experiences with AI in recruitment. Participant recruitment is supported by a Latvian recruitment agency, which grants access to a relevant and diverse candidate base. Expected findings include identifying distinct readiness profiles among Latvian youth, revealing both areas of competence and significant gaps in knowledge or confidence. Attitudinal differences and inequalities in access to digital resources are also anticipated. The proposed methodology offers a replicable framework for assessing AI readiness at the national level and is intended to guide HR professionals, educators, and policymakers in developing effective strategies to support youth adaptation to AI-driven workplace transformations.